Microstructure evolution and mechanical property response via 3D printing parameter development of Al–Sc alloy - C. N. Kuo; C. K. Chua; P.C. Peng; Y. W. Chen; S. L. Sing; S. Huang; Y. L. Su (Virtual and Physical Prototyping, 2020)
Three-dimensional (3D) printed Sc-modified Al alloy by powder bed fusion (PBF) provides significant strength and ductility without hot tearing during the process. This kind of 3D-printable high specific strength materials exhibits great potential in lightweight applications. Due to the lesser design limitation through the 3D printing process, the degree of lightweight is greatly affected by the specific strength of the materials. Hence, to further improve the mechanical properties of the material through process optimisation or post-treatment is of great importance. Microstructure feature variations due to different processing parameters are well known for traditional processes and materials. This study explores the parameter–microstructure–performance relationship of 3D printed Sc-modified Al alloys from the perspective of melt pool interactions. According to the stress concentration effect and Hall–Petch effect, the mechanical properties of the 3D printed materials vary greatly depending on the difference in defect size, shape and grain size.